2023
DOI: 10.1136/bmjopen-2022-069656
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal individualised intervention to prevent functional decline after stroke: protocol of a randomised controlled trial on long-term follow-up after stroke (LAST-long)

Abstract: IntroductionMultimodal interventions have emerged as new approaches to provide more targeted intervention to reduce functional decline after stroke. Still, the evidence is contradictory. The main objective of the Life After Stroke (LAST)-long trial is to investigate if monthly meetings with a stroke coordinator who offers a multimodal approach to long-term follow-up can prevent functional decline after stroke.Methods and analysisLAST-long is a pragmatic single-blinded, parallel-group randomised controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Furthermore, the importance of rehabilitation after orthopedic surgery or acute events such as stroke or myocardial infarction cannot be overstated. Studies have shown that early and intensive rehabilitation can lead to improved outcomes in terms of functional status, pain management, and overall quality of life [ 9 , 10 , 11 ]. Rehabilitation plays a crucial role in the recovery of patients, improving their quality of life and reducing the risk of complications and readmissions.…”
mentioning
confidence: 99%
“…Furthermore, the importance of rehabilitation after orthopedic surgery or acute events such as stroke or myocardial infarction cannot be overstated. Studies have shown that early and intensive rehabilitation can lead to improved outcomes in terms of functional status, pain management, and overall quality of life [ 9 , 10 , 11 ]. Rehabilitation plays a crucial role in the recovery of patients, improving their quality of life and reducing the risk of complications and readmissions.…”
mentioning
confidence: 99%